Student’s Self Check In Revising An Essay - Anggi Rahmanida Nst; Aisyah Rizqa Fitri Srg; Ardina Khoirunnisa; Utami Dewi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
This research is based on the need to investigate students' abilities in writing essays. Essay is defined as a short essay containing the author's opinion or argument about a topic. Usually, someone writes an essay because he wants to give an opinion on a problem or phenomenon that occurs in society. Essay writers, or often called essayists, can also explore a topic or issue and provide responses and opinions on the topic or issue discussed. Self-check of students in revising essays helps students to increase self-confidence and be able to revise essays properly and correctly. An essay is a part (piece) of a piece of writing, but an essay can also be interpreted as a complete short essay. Therefore, essays are a type of writing that is often used as a test tool to measure one's intelligence. A knowledgeable person will be able to convey his ideas in a coherent, logical and interesting way. The more often someone reads, the more likely they are to be able to write a good essay.